Edukasi dan Pemanfaatan Minyak Jelantah sebagai Upaya Pencegahan Pencemaran Lingkungan - Pohan, Heni Mulyani; Harahap, Fatma Suryani; Elisa, Elisa; Sormin, Ayunda Sabrina; Sahara, Nur; Hrp, Hafnita (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2023)
The lack of knowledge and public awareness of the dangers of direct disposal of cooking oil waste is one of the reasons for doing service to housewives in Pasar Hilir village, Mandailing Natal regency. The purpose of this service is to educate housewives about the dangers of consuming used cooking oil and disposing of used cooking oil waste into local waters as well as providing training workshops on making one of the household products, namely soap, by utilizing used cooking oil waste that can be reused for washing in daily life. Key words : cooking oil waste, soap, training